Generation Why how boomers can lead and learn from millennials and Gen Z - Moore, Karl. (London McGill Queens University Press, 2023)
Perhaps more than ever before, young people entering the workforce are searching for meaning and authenticity in their careers. This book helps managers understand the postmodern worldview held by generation Z and younger millennials, how it influences their behaviour at work, and how they want to be led in the workplace.Karl Moore takes a practical and down-to-earth approach to understanding what drives millennials and generation Z and how the education system they were brought up in has informed their worldview. Based on hundreds of interviews conducted with under-thirty-year-olds across Canada, the United States, Japan, Iceland, the United Kingdom, and elsewhere, as well as interviews with executives to gain their perspectives on changing dynamics in the workplace, Generation Why provides a thorough study of these generations? ideas about truth, hierarchy, and leadership.Focusing on listening, purpose, reverse mentoring, feedback, and how people relate to each other in the workplace, Generation Why provides the essential tools for effectively working with millennials and generation Z and unlocking their full professional potential.
Includes index
Keywords: Leadership